Total Synthesis of Two Pyrrole Spiroketal Alkaloids: Pollenopyrroside A and Capparisine B - Cao, Zhi; Li, Yueqing; Wang, Shisheng; Guo, Xiuhan; Wang, Liu; Zhao, Weijie (Synlett, 2015)
Pollenopyrroside A and capparisine B, two diastereoisomers of pyrrole spiroketal alkaloids isolated from Brassica campestris pollen and Capparis spinosa, were synthesized by an improved microwave-assisted bishydroxymethylation of pyrrole and acid-catalyzed spirocyclization as key steps with total yields of 2.7 and 8.8%, respectively.
Keywords: alkaloids; spiroketals; natural products; total synthesis; microwave-assisted reaction